Analisa Dampak Fluktuasi Nilai Tukar Rupiah terhadap Arus Ekspor dan Impor Indonesia Tahun 2023-2025 - Najla Aqilah; Naysilla Chairani; Nisrina Zasmin; Muhammad Alzidan Herdiansyah; Ahmad Setiawan Nuraya (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the impact of Rupiah exchange rate fluctuations on Indonesia’s export and import flows during the 2023–2025 period. Exchange rate stability plays a crucial role in maintaining international trade performance, particularly for developing countries with open economic systems such as Indonesia. The study employs a quantitative approach using monthly secondary data obtained from Bank Indonesia, the Ministry of Trade, and other official sources. Multiple linear regression analysis is utilized to examine the relationship between the Rupiah exchange rate, inflation, exports, and imports. The findings indicate that exchange rate fluctuations did not have a statistically significant effect on Indonesia’s exports during the observation period. Export performance was influenced more strongly by external factors such as global commodity prices, international demand, and geopolitical conditions. In contrast, the exchange rate had a positive and significant impact on imports, reflecting Indonesia’s continued dependence on imported raw materials and capital goods. The results suggest that Rupiah depreciation has not been sufficient to reduce import activities due to the inelastic nature of industrial demand. Therefore, maintaining exchange rate stability, strengthening domestic industries, and promoting import substitution policies are essential to enhance Indonesia’s economic resilience and trade sustainability amid global uncertainty.